A nanostructured lipid system as a strategy to improve the in Vitro antibacterial activity of copper(II) complexes - Da Silva, Patricia B. [UNESP]; Bonifácio, Bruna V. [UNESP]; Frem, Regina C. G. [UNESP]; Netto, Adelino V. Godoy [UNESP]; Mauro, Antonio E. [UNESP]; Da Costa Ferreira, Ana M.; De Lopes, Erica O. [UNESP]; Raddi, Maria S. G. [UNESP]; Bauab, Tais M. [UNESP]; Pavan, Fernando R. [UNESP]; Chorilli, Marlus [UNESP] (MDPI, 2015)
The aim of this study was to construct a nanostructured lipid system as a strategy to improve the in vitro antibacterial activity of copper(II) complexes. New compounds with the general formulae [CuX2(INH)2]·nH2O (X = Cl- and n = 1 (1); X = NCS- and n = 5 (2); X = NCO- and n = 4 (3); INH = isoniazid, a drug widely used to treat tuberculosis) derived from the reaction between the copper(II) chloride and isoniazid in the presence or absence of pseudohalide ions (NCS- or NCO-) were synthesized and characterized by infrared spectrometry, electronic absorption spectroscopy, electron paramagnetic resonance (EPR) spectroscopy, elemental analysis, melting points and complexometry with 2,2′,2″,2″-(Ethane-1,2-diyldinitrilo)tetraacetic acid (EDTA). The characterization techniques allowed us to confirm the formation of the copper(II) complexes. The Cu(II) complexes were loaded into microemulsion (MEs) composed of 10% phase oil (cholesterol), 10% surfactant [soy oleate and Brij® 58 (1:2)] and 80% aqueous phase (phosphate buffer pH = 7.4) prepared by sonication. The Cu(II) complex-loaded MEs displayed sizes ranging from 158.0 ± 1.060 to 212.6 ± 1.539 nm, whereas the polydispersity index (PDI) ranged from 0.218 ± 0.007 to 0.284 ± 0.034. The antibacterial activity of the free compounds and those that were loaded into the MEs against Staphylococcus aureus ATCC® 25923 and Escherichia coli ATCC® 25922, as evaluated by a microdilution technique, and the cytotoxicity index (IC50) against the Vero cell line (ATCC® CCL-81™) were used to calculate the selectivity index (SI). Among the free compounds, only compound 2 (MIC 500 μg/mL) showed activity for S. aureus. After loading the compounds into the MEs, the antibacterial activity of compounds 1, 2 and 3 was significantly increased against E. coli (MIC's 125, 125 and 500 μg/mL, respectively) and S. aureus (MICs 250, 500 and 125 μg/mL, respectively). The loaded compounds were less toxic against the Vero cell line, especially compound 1 (IC50 from 109.5 to 319.3 μg/mL). The compound 2- and 3-loaded MEs displayed the best SI for E. coli and S. aureus, respectively. These results indicated that the Cu(II) complex-loaded MEs were considerably more selective than the free compounds, in some cases, up to 40 times higher.
Keywords: Antibacterial activity; Copper(II) complexes; Escherichia coli; Nanostructured lipid system; Staphylococcus aureus